Migration aspirations and the perceptions of the political, economic and social environment in Africa - Marc Helbling; Sandra Morgenstern (International Migration, 2023)
While much research has investigated how objective pull factors in the destination countries affect migration movements, and how subjective push factors affect migration aspirations, we know little about the interrelationship between subjective and objective factors. This paper therefore examines how people's perceptions of their political, economic and social structural environment affect their migration aspirations and to what extent these perceptions are determined by the objective situation in a country. Accounting for individual perceptions is important because individuals may be affected by structural factors to different degrees, and their knowledge of the objective situation may vary. Perceptions may also be affected by individuals' norms and values as well as people's different expectations. This study is based on data from Round 7 of the Afrobarometer survey, fielded between 2016 and 2018 in 34 African countries. Our findings show that positive perceptions of the structural environment are related to lower migration aspirations and that this relationship is only partly dependent on the objective situation in a country.
Keywords: 300